WHO IS THE MOST AUTHORIZED TO ERADICATE ILLEGAL FINANCIAL INSTITUTION ? - Suwinto Johan; Gunard LIe; Amad Sudiro (Universitas Labuhanbatu, 2023)
Illegal financial institutions have repeatedly appeared and disappeared in the community. Illegal banks or savings institutions disguise their businesses as travel agents or public fund savings institutions calledÂ arisan. At the moment, there have been emerging illegal online loan institutions (Pinjol). In 2021, illegal online loans (Pinjol) become a trending topic in Indonesia. Illegal lending has become a long-standing issue in society. The authorities have carried out the eradication of illegal lending. However, illegal borrowing is never completely eradicated and is always present in the community. Illegal borrowing has also caused a lot of community problems. This research aims to examine the illegal borrowing in the midst of society. This research uses a normative juridical method. This research concludes that eradicating illegal lending is the responsibility of the police, not the responsibility of the Indonesian Financial Services Authority (OJK). Even though illegal lenders operate in the financial industry, the Indonesian Financial Services Authority has no authority over the illegal financial industry. The authority of the Indonesian Financial Services Authority has been confirmed in Law of the Republic of Indonesia Number 21 of 2011. The illegal financial industry does not only exist in the financial technology industry, but has also emerged repeatedly in the conventional financial industry, such as illegal banks, fraudulent investments, and credit unions.